Controlling Cu2ZnSnS4 (CZTS) phase in microwave solvothermal synthesis. Issue 44 (1st November 2017) - Pinto, Alexandre H.; Shin, Seung Wook; Isaac, Elianna; Knutson, Theodore R.; Aydil, Eray S.; Penn, R. Lee
Abstract : The crystalline phase of Cu2 ZnSnS4 can be controlled between kesterite and wurtzite by varying the initial oxidation state of Cu and Sn ions, and the source of the sulfur excess in a microwave solvothermal method. Abstract : The semiconductor Cu2 ZnSnS4 (CZTS) is a promising sustainable photovoltaic material and colloidal dispersions of wurtzite or kesterite CZTS nanocrystals are often used to make thin polycrystalline films for solar cells. This requires control of the nanocrystal phases via the synthesis. We studied the microwave-assisted solvothermal synthesis of CZTS nanocrystals from metal salts and thiourea in ethylene glycol in the presence of various excess sulfur sources. Relative fractions of the kesterite and wurtzite phases depend on the excess sulfur source, the oxidation state of Sn, and the sulfur-to-total-metal -cation (S : M) ratio used in the synthesis. When the excess sulfur source contains an amino group, a Zn–Sn intermediate forms and allows the CZTS phase to be varied between kesterite and wurtzite via the Sn initial oxidation state and S : M ratio. When the excess sulfur source contains an amino group, synthesis using Sn(ii ) salts and low S : M (1.9) favors the formation of the wurtzite phase, whereas synthesis using high S : M ratio (>4) favors the formation of the kesterite phase. Only the kesterite phase is obtained when Sn(iv ) reagent is used, regardless of S : M ratio. When the excess sulfur source does not have an amino group, only the wurtzite phase is obtained under the conditions studied, regardless of the oxidation state of the Sn precursor or the S : M ratio; in these cases, the Zn–Sn intermediate does not form and the precursor to wurtzite appears to be copper sulfide.